2017
DOI: 10.1080/17434440.2017.1384695
|View full text |Cite
|
Sign up to set email alerts
|

Orbital atherectomy for the treatment of severely calcified coronary lesions: evidence, technique, and best practices

Abstract: The presence of severe coronary artery calcification is associated with higher rates of angiographic complications during percutaneous coronary intervention (PCI), as well as higher major adverse cardiac events compared with non-calcified lesions. Incorporating orbital atherectomy (OAS) for effective preparation of severely calcified lesions can help maximize the benefits of PCI by attaining maximal luminal gain (or stent expansion) and improve long-term outcomes (by reducing need for revascularization). Areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 77 publications
(107 reference statements)
2
63
0
1
Order By: Relevance
“…The optimal results presented here are likely due to the unique mechanism of action of OA and Chocolate balloon angioplasty. As previously reviewed, OA has an orbital and differential sanding mechanism that reduces plaque burden, creating vessel compliance while minimizing damage to the medial layer of the vessel . The Chocolate balloon consists of a mounted nitinol constraining structure specifically designed for uniform, controlled inflation and rapid deflation, resulting in atraumatic dilatation without the need for cutting or scoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal results presented here are likely due to the unique mechanism of action of OA and Chocolate balloon angioplasty. As previously reviewed, OA has an orbital and differential sanding mechanism that reduces plaque burden, creating vessel compliance while minimizing damage to the medial layer of the vessel . The Chocolate balloon consists of a mounted nitinol constraining structure specifically designed for uniform, controlled inflation and rapid deflation, resulting in atraumatic dilatation without the need for cutting or scoring.…”
Section: Discussionmentioning
confidence: 99%
“…The Diamondback 360 coronary OA system (Cardiovascular Systems, Inc. [CSI], St Paul, MN) was utilized in all cases analyzed. As previously reviewed, the mechanism of this device has been shown to be useful in the treatment of severely calcified, noncompliant coronary lesions prior to appropriate percutaneous transluminal coronary angioplasty and adequate stent deployment …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Orbital atherectomy (OA) is a newly FDA approved device for treatment of severely calcified coronary lesions which works on the principle of elliptical burr movement. ORBIT II clinical trial evaluated the safety of OA in de novo calcified coronary lesions and demonstrated that complication rate was comparable to historical controls of rotational atherectomy (RA); however, bifurcation lesions were excluded from the trial …”
Section: Introductionmentioning
confidence: 99%
“…ORBIT II clinical trial evaluated the safety of OA in de novo calcified coronary lesions and demonstrated that complication rate was comparable to historical controls of rotational atherectomy (RA) 11 ; however, bifurcation lesions were excluded from the trial. 12 The aim of the study was to identify the predictors of SB compromise in calcified bifurcation PCI with OA using 3-dimensional (3D) quantitative coronary angiography (QCA) and OCT imaging data.…”
Section: Introductionmentioning
confidence: 99%